Manajemen Implementasi Program Pembinaan Karakter Islami melalui Kegiatan ROHIS di Madrasah Al-Washliyah Stabat - Ellena Simarmata; Nurlaila Sholeha; Wartini; Pratiwi Septia Ningsih; Juliani Putri (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study analyzes the management of implementing Islamic character-building programs through ROHIS activities at Madrasah Al-Washliyah Stabat. Using a descriptive qualitative approach, data were collected through observation, interviews, and document review. The results show that the implementation of ROHIS is managed through structured planning, including annual activity design, selection of mentors, and student coordination. The organizing stage involves the division of tasks among ROHIS officers and collaboration between teachers and students. Program implementation includes regular Qur’an studies, mentoring, speech practice, daily prayer memorization, and social activities. Monitoring is carried out continuously through attendance, mentoring reports, and direct evaluation by advisors. This managerial system contributes significantly to strengthening students’ Islamic character, especially in discipline, responsibility, politeness, and religious commitment. ROHIS becomes an effective medium for integrating Islamic values into students’ daily behavior through well-managed and sustainable activities. Penelitian ini menganalisis manajemen implementasi program pembinaan karakter Islami melalui kegiatan ROHIS di Madrasah Al-Washliyah Stabat. Pendekatan kualitatif deskriptif digunakan melalui observasi, wawancara, dan telaah dokumen. Hasil penelitian menunjukkan bahwa implementasi ROHIS dikelola melalui perencanaan terstruktur meliputi penyusunan program tahunan, penetapan pembina, serta koordinasi pengurus dan siswa. Tahap pengorganisasian dilakukan dengan pembagian tugas pengurus ROHIS serta kerja sama antara guru dan peserta didik. Pelaksanaan program mencakup kajian Al-Qur’an, mentoring, latihan ceramah, hafalan doa harian, dan kegiatan sosial. Pemantauan dilakukan secara berkelanjutan melalui absensi, laporan kegiatan, dan evaluasi pembina. Sistem manajemen ini berkontribusi besar dalam memperkuat karakter Islami siswa, terutama dalam hal kedisiplinan, tanggung jawab, kesopanan, dan komitmen beribadah. ROHIS terbukti menjadi media efektif dalam menanamkan nilai Islam melalui kegiatan yang terkelola dan berkesinambungan.